The Pedagogy of Experience: A Case Study of Pilgrimage as Experiential Learning - Dent C. Davis (Adult Education Research Conference, 2007)
Findings from this case study of the extended pilgrimage of an ecumenical group of forty mid-career pastors to the Holy Land suggest how importance of an ecological understanding of experiential learning that includes insight, whole person learning, context, spirituality and transformation as aspects of experiential learning.